Enhancing performance: unveiling the physiological impact of submaximal and supramaximal tests on mixed martial arts athletes in the -61 kg and -66 kg weight divisions - Gonçalves, A. F.; Miarka, B.; Maurício, C. A.; Teixeira, R. P. A.; Brito, C. J.; Pérez, D. I. V.; Slimani, M.; Znazen, H.; Bragazzi, N. L.; Reis, V. M. (Frontiers in Physiology, 2024)
This study delves into the intricate details of Mixed Martial Arts (MMA) by examining key variables such as maximal oxygen uptake (VO2 peak), aerobic energy (EAER), anaerobic energy (EAN), and accumulated O2 deficit (DOA). By investigating associations and comparing athletes in the -61 kg bantamweight and -66 kg featherweight weight divisions, we aim to shed light on their physiological characteristics. The sample consisted of 20 male volunteers separated into two paired groups: ten athletes in the category up to 61 kg (age: 27.7 ± 5.9 years old, height: 170.9 ± 3.4 cm, body mass: 72.8 ± 1.4 kg, fat percentage: 9.5% ± 3.0%, professional experience: 7.5 ± 7.1 years) and ten athletes up to 66 kg (age: 27.6 ± 2.9 years old, height: 176.0 ± 5.5 cm, body mass: 77.0 ± 1.5 kg, fat percentage: 7.85% ± 0.3%, professional experience: 5.5 ± 1.5 years). Remarkably, our findings revealed striking similarities between the two weight divisions. Furthermore, we discovered a negative correlation between VO2 peak and the number of MMA fights, indicating a potential impact of professional experience on aerobic capacity (r = -0.65, p < 0.01). Additionally, the number of fights exhibited negative correlations with anaerobic energy (r = -0.53, p < 0.05) and total energy cost (r = -0.54, p < 0.05). These results provide valuable insights for designing training programs in the context of MMA. While training both weight divisions together can be beneficial, it is equally crucial to incorporate specific weight-class-focused training to address each division`s unique physical demands and requirements.